Nanotechnology and neurophysiology. (June 2015) - Angle, Matthew R; Cui, Bianxiao; Melosh, Nicholas A
Highlights: Nanofabrication is capable of patterning devices at the same length-scales as cellular components (i.e. 10 s of nanometers). Nanoscale devices can be used to measure intracellular electrical activity. The current limitation for these technologies is their ability to form tight seals with the plasma membrane. The area of nano–bio interactions is being recognized as increasingly important, and as our understanding improves as to the fundamental interactions between nanoscale inorganic devices and cells, the next generation of intracellular tools will undoubtedly become more powerful. Abstract : Neuroscience would be revolutionized by a technique to measure intracellular electrical potentials that would not disrupt cellular physiology and could be massively parallelized. Though such a technology does not yet exist, the technical hurdles for fabricating minimally disruptive, solid-state electrical probes have arguably been overcome in the field of nanotechnology. Nanoscale devices can be patterned with features on the same length scale as biological components, and several groups have demonstrated that nanoscale electrical probes can measure the transmembrane potential of electrogenic cells. Developing these nascent technologies into robust intracellular recording tools will now require a better understanding of device–cell interactions, especially the membrane–inorganic interface. Here we review the state-of-the art in nanobioelectronics, emphasizing the characterization and design of stable interfaces between nanoscale devices and cells.